Interleukin-29 modulates proinflammatory cytokine production in synovial inflammation of rheumatoid arthritis - Wang, Fang (BioMed Central, 2012)
INTRODUCTION: The immunoregulatory function of interleukin (IL)-29 has recently been recognized. However, little is known about the involvement of IL-29 in the pathogenesis of rheumatoid arthritis (RA). This study aimed to examine the expression profiles of IL-29 in blood, synovial fluid (SF) and synovium in RA patients and investigate the effect of IL-29 on cytokines production in RA synovial fibroblasts. METHODS: The transcript levels of IL-29 and its specific receptor IL-28Rα in peripheral blood mononuclear cells (PBMC) and synovium were determined by real-time reverse transcription-polymerase chain reaction (real-time PCR). The concentrations of IL-29 in serum and synovial fluid (SF) were quantified by enzyme-linked immunoassay (ELISA), and the correlation of serum IL-29 levels with disease activity in RA patients was investigated. Furthermore, the expression of IL-29 in RA synovium was examined by immunohistochemistry and double immunofluorescence analysis. Finally, the expression of IL-6, IL-8, IL-10, IL-17 and matrix metalloproteinase-3 (MMP-3) in synovial fibroblasts upon IL-29 stimulation was determined by real-time PCR. RESULTS: IL-29 and IL-28Rα mRNA expression in PBMC was significantly increased in patients with RA compared with healthy controls (HC). The serum levels of circulating IL-29 were higher in RA than those in HC. Increased IL-29 levels were detected in RA SF when compared with osteoarthritis (OA) SF. However, serum IL-29 levels showed no significant correlation with RA disease activity. IL-29 was mostly expressed in the lining region of RA synovium. Moreover, IL-29 was expressed predominately in synovial macrophages and fibroblasts. RA synovial fibroblasts exposed to IL-29 specifically upregulated IL-6, -8 and MMP-3 but downregulated IL-10. CONCLUSIONS: The findings in the present study indicate, for the first time, that IL-29 is dysregulated in patients with RA, which may contribute to the RA pathogenesis via inducing the production of proinflammatory cytokines, chemokines or matrix metalloproteinases in synovial fibroblasts.